2015
DOI: 10.1128/jvi.00563-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activation of Human NK Cells by Treatment with an Interleukin-15 Superagonist Potently Inhibits Acute In Vivo HIV-1 Infection in Humanized Mice

Abstract: T he crucial role of the human immunodeficiency virus (HIV)-specific T cell and antibody response mounted by the adaptive immune system to control HIV-1 infection is well established (1). However, during acute infection, viremia is not controlled because it takes several weeks after the initiation of infection for the adaptive immune response to activate and clonally expand sufficient numbers of HIV-1-specific T cells and B cells to suppress HIV-1 infection (2). This delay in the mobilization of the adaptive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 62 publications
1
90
0
Order By: Relevance
“…6,25,26 Therefore, it is possible that IL-15 presents in the circulation of NOD.scid.Il15ra -/-recipients can bind to IL-15Ra present on donor cells and trans-present IL-15 to autoreactive effector CD8 1 T cells. To address the role of donor-derived IL15Ra, we adoptively transferred splenocytes from diabetic NOD.…”
Section: Resultsmentioning
confidence: 99%
“…6,25,26 Therefore, it is possible that IL-15 presents in the circulation of NOD.scid.Il15ra -/-recipients can bind to IL-15Ra present on donor cells and trans-present IL-15 to autoreactive effector CD8 1 T cells. To address the role of donor-derived IL15Ra, we adoptively transferred splenocytes from diabetic NOD.…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with recent data that ALT-803 reverses viral latency in vitro, 17 it could potentially mediate both the "shock" and the "kill" in eradication strategies. Finally, given that ALT-803 also potently activates NK cells and increases their cytolytic potential, 14,16 it could also be combined with broadly neutralizing antibodies to mobilize both cytotoxic CD8 1 T-cell-and NK-mediated antibody-dependent cell-mediated cytotoxicity to clear latent virus. Cumulatively, these 3 effects suggest that ALT-803 is a formidable addition to the HIV eradication armament.…”
Section: Cd8 T Cellsmentioning
confidence: 99%
“…8,9,14,15 These findings have recently been extended to HIV infection, where ALT-803-activated NK cells inhibit acute HIV infection in vivo, 16 and ALT-803 also reactivates latent virus in vitro. 17 In this study, we demonstrated that ALT-803 significantly enhanced lymphocyte proliferation and activation, specifically CD16…”
mentioning
confidence: 99%
“…As an alternative or adjunct to blocking inhibitory pathways, CD8 + T cell function can be enhanced by the provision of cytokines or other immunostimulatory agents. IL-15 agonists are of particular interest in this regard, having been shown to enhance CD8 + T cell and NK cell activity in a number of preclinical models (135)(136)(137)(138)(139), and the IL-15 superagonist ALT-803 is moving into a clinical trial in cART-treated HIV-infected subjects (ClinicalTrials.gov identifier: NCT02191098). Other immunostimulatory agents include TLR-2 agonists, which reverse CD8 + T cell exhaustion and enhance both tumor-and pathogen-specific T cell responses in vivo (140)(141)(142), and agonistic Abs against 41BB or CD40 (143-145), among others.…”
Section: Cd8 + T Cell Compartmentalization and The Viral Reservoirmentioning
confidence: 99%